2020
DOI: 10.4018/978-1-5225-8270-0.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Towards Customer Relationship Marketing

Abstract: The chapter adopts a theoretical approach to exploring the existing literature on emotional intelligence models and customer relationship marketing concept with the aim of proposing a ‘new' conceptual model interlinking emotional intelligence (EI) and customer relationship marketing (CRM). The proposed conceptual model will then be re-developed on the basis of the findings that will emerge from a qualitative case study research carried out in the Lebanese retail banking sector. The fact that the focus of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…EI has gained a great deal of attention over the past decades (Shao et al , 2015; Al Khoury et al , 2018; Al Khoury et al , 2019). Salovey and Mayer (1990, p. 189) were the first to define EI, suggesting that EI is:…”
Section: Literaturementioning
confidence: 99%
“…EI has gained a great deal of attention over the past decades (Shao et al , 2015; Al Khoury et al , 2018; Al Khoury et al , 2019). Salovey and Mayer (1990, p. 189) were the first to define EI, suggesting that EI is:…”
Section: Literaturementioning
confidence: 99%
“…The research, on which this paper is founded, addresses especially Tudor's (2015) call for exploring the practice of EI within the banking sector, and, specifically, the Lebanese retailbanking sector. Kearney et al (2017) and Al Khoury et al (2019) highlighted the need to produce empirical data to explore employees' EI skills and their impact on customer service and satisfaction. The research also attempts to bridge the gap identified by Hejase et al (2012), Geha (2015) and El-Chaarani (2013) in the extant literature, concerning the need to relate EI to other business concepts such as customer relationship marketing.…”
Section: Research Background and Gapsmentioning
confidence: 99%